John C. Parkin, Archives, and Photography Reflections on the Practice and Presentation of Modern Architecture - McMordie, Michael; Fraser, Linda; Simmins, Geoffrey (Art in Profile, 2013)
Architectural practice in post-World War II Canada brought substantial change to the face of the Canadian built environment, led by the contribution of John C. Parkin. As senior partner at the Toronto-based architectural firm John B. Parkin Associates (no relation) from 1947 to the 1970s, Parkin oversaw the creation of a large number of modernist projects, including hospitals, airports, schools, shopping malls, and factories, and received national recognition for his contributions. This richly illustrated book includes an interview with John C. Parkin and essays that examine the incorporation of art in built architecture, the influence of architectural photography in defining Modern architecture to a Canadian public, the importance of architectural archives, and the corporate structure of a large, highly successful Canadian architectural firm.